"Ngalap Berkah" for Political Power: Tomb Pilgrimage as Spiritual Legitimacy in Yogyakarta's Royal Heritage Sites - Wasisto Raharjo Jati (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2026)
This article examines tomb pilgrimage, known in Indonesian, particularly Javanese society, as ziarah—not merely as an act of praying for the deceased but as a search for spiritual blessings and power. This special intention motivates the present study to treat tombs as more than cultural heritage sites, recognising them as sources of political fortune as well. Framed by the concepts of pulung and wahyu (divine blessing), the study examines the relationship between tomb pilgrimage and political fortune. Pulung is widely believed to be an abstract symbol of divine power bestowed upon candidates who succeed in elections; here, pulung/wahyu is understood as sacred power associated with deceased royalty, which political aspirants seek to appropriate to bolster their own legitimacy. Fieldwork was conducted at three cultural heritage sites in Yogyakarta, i.e., Wotgaleh, Kotagede, and Imogiri, each regarded as sacred owing to its status as a royal tomb complex, and each attracting numerous visitors, including political candidates, politicians, and bureaucrats, particularly on specific auspicious nights. Data were collected through qualitative methods, drawing on interview transcripts cross-referenced with documentary evidence. The data were derived from in-depth interviews with 30 purposively selected informants, comprising pilgrims and tomb caretakers, together with relevant documentary analysis. The findings indicate that tomb pilgrimage functions as a means of seeking blessings for political fortune, consistent with the prevailing belief that power derives not only from the microcosm but also from the macrocosm. The study concludes that although political competition is a rational contest for power, spiritual blessings continue to play an important role in its pursuit.